Non-Linear Regresion And Bisection Method Numerical Analysis of Humidity And Temperature Relationships - Lulut Alfaris; Ruben Cornelius Siagian; Budiman Nasution; Goldberd Harmuda Duva Sinaga; Indah Indah (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
This study aims to analyze the correlation of temperature and humidity based on climatological data from Kuningan, West Java province, Indonesia, using non-linear regression and numerical analysis using the bisection method. In studying the education curriculum in Indonesia, most of them have studied linear regression, but only within certain limits, namely linear and multiple. It is still rare for students to use non-linear regression in their analysis. This paper will explain the analysis using non-linear regression as a source of data and equations in numerical analysis so that it can be applied in the context of the numerical bisection method. As for data processing and numerical analysis, Microsoft Excel is used. The authors combined the two variables in the non-linear analysis and used geometric equations for the numerical quotient analysis. The author displays the results of numerical graphs and real-time data obtained from the source "Data access viewer NASA."